Sistem Pengkabut dan Intermitten Lighting Colour Otomatis untuk Optimalisasi Budidaya Microgreen Organik - Hіlmі А'іnі Nurthoyіbаh; Ayu Fіtrіаnі; Rеzа Zulіаnsyаh Sobіrіn; Rаіhаn Putrа Dwіyаnа; Аіf Аl Zulfа; Hеrіk Sugеru (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2025)
Infrastructure development in major cities in Indonesia is growing rapidly, converting agricultural land into non-agricultural land. Urban farming is the activity of cultivating plants on limited land in urban areas to improve family nutrition or food security. Urban agriculture serves as a strategy to address the gap between food production and population growth rates. Microgreens are vegetables harvested very young, typically 7-14 days after germination. Microgreen cultivation can be done on limited land, such as in urban areas. With the continuous advancement of technology, the use of technology-based agricultural systems is highly needed, one of which is the use of IoT (Internet of Things) technology. AMICRON is a modified growth environment to optimize organic microgreen cultivation by applying mist systems and intermittent lighting color. The development of the AMICRON tool involves several stages, including preparation, design creation, product manufacturing, planting processes, product feasibility testing, and evaluation. Microgreen planting is carried out both inside and outside the AMICRON tool. Microgreens planted inside the AMICRON tool with intermittent lighting color lamps result in faster germination and harvesting times than those planted outside the AMICRON tool or those using grow lights.